Financial applications of semidefinite programming: a review and call for interdisciplinary research. (27th September 2019) - Gepp, Adrian; Harris, Geoff; Vanstone, Bruce
Abstract: Optimisation problems in finance commonly have non‐linear constraints for which previous solutions have required unrealistic assumptions. However, many of these can be efficiently solved as semidefinite programming (SDP) problems, which have less restrictive assumptions. Through review of the literature that uses SDP in finance, two major research streams are identified: portfolio optimisation and option pricing. Nevertheless, many finance researchers are unaware of SDP. One possible reason is that this research is often published in non‐finance journals. This paper aims to better integrate the SDP research to promote wider use of current findings and further interdisciplinary research, particularly in environmental finance.